Graduate Lecturer’s Work Engagement and the Evaluation Carried Out by their Students in an Ecuadorian University - Raza-Carrillo, Diego Fabián (2020)
The goal of this research is to identify if there is a difference in the evaluation that graduate students make of their teachers when they report different levels of work engagement in their dimensions of vigor, dedication and absorption. The students and teachers who received and taught in the third quarter of the 2016-2017 school year were taken as a reference in an academic area of a graduate university in Ecuador. The evaluations of teachers carried out by the students at the end of the term were used, and they were contrasted with the levels of work engagement reported by their teachers before the beginning of the term. The methodology was quantitative in nature: statistical tests were applied to test the significance of the differences found in the different analyzes, and the result was that teachers who reported higher values of vigor were evaluated with higher scores in their ability to generate an atmosphere of participation in the classroom. The conclusion of the study is then that one of the dimensions of proffesors’ work engagement had an impact on one of the components of the evaluation that students carried out on their lecturers in the selected sample.